Association between serum 25-hydroxyvitamin D levels and the presence and severity of striae gravidarum in primigravid women - AKDENİZ, ESRA (WILEY, 2020)
Background Striae gravidarum (SG) are a form of scarring on the skin observed during pregnancy and an important cosmetic problem. Vitamin D plays an important role in the skin. Aims To assess the association between serum 25-hydroxyvitamin D (25(OH)D) levels and the presence and severity of SG in primigravid women. Methods The study included 91 primigravid women at the gestational age of 36-41 weeks. Patients were examined and divided into two groups with respect to whether they had SG or not. Striae were scored using the numerical scoring system of Atwal et al. The serum 25(OH)D levels were evaluated. Results While 55 patients (60.5%) had SG, 36 (39.5%) did not. The mean serum 25(OH)D level of women with SG was 17.69 +/- 9.81 ng/mL and of women without SG was 21.18 +/- 11.71 ng/mL. There was no statistically significant difference between two groups (P = .144). Multivariate logistic regression analysis has shown that women who have normal values of serum 25(OH)D (>= 30 ng/mL) have a lower risk of having SG than women who have scarce levels of serum 25(OH)D (<20 ng/mL) after adjusting for confounding factors (adjusted odds ratio = 0.18, 95% confidence interval: 0.04-0.72, P = .015). According to the results of the linear-by-linear test, the association between serum 25(OH)D levels and the severity of SG was not found significant (P = .82). Conclusions This is the first study to show that having normal values of serum 25(OH)D is linked to a lower risk of having SG than scarce levels. Therefore, management of vitamin D deficiency might help prevent SG in primigravid women.
Keywords: disease severity; pregnancy; stretch marks; striae gravidarum; vitamin D; VITAMIN-D; PREGNANT-WOMEN; SMOKING